Theoretical Analysis on the Measurement Errors of Local 2D DIC: Part II Assessment of Strain Errors of the Local Smoothing Method–Approaching an Answer to the Overlap Question. (8th January 2016) - Wang, Y.; Lava, P.; Reu, P.; Debruyne, D.
Abstract: In this paper, the strain error of subset‐based two‐dimensional digital image correlation (DIC) is theoretically derived. Analytical solutions are provided to estimate the strain error. A dimensionless factor is proposed, namely the overlap magnifier, which reveals the dependency of the strain error on the DIC regularisation parameters, that is, subset size, step size and strain window size. The derived equations are validated numerically and experimentally. The estimated random strain error is in good accordance with the experimental data. The proposed derivation can be readily extended to stereo DIC.